Guidelines for the Management of Severe Traumatic Brain Injury, Fourth Edition. Issue 1 (20th September 2016) - Carney, Nancy; Totten, Annette M.; O'Reilly, Cindy; Ullman, Jamie S.; Hawryluk, Gregory W.J.; Bell, Michael J.; Bratton, Susan L.; Chesnut, Randall; Harris, Odette A.; Kissoon, Niranjan; Rubiano, Andres M.; Shutter, Lori; et al.
Abstract: The scope and purpose of this work is 2-fold: to synthesize the available evidence and to translate it into recommendations. This document provides recommendations only when there is evidence to support them. As such, they do not constitute a complete protocol for clinical use. Our intention is that these recommendations be used by others to develop treatment protocols, which necessarily need to incorporate consensus and clinical judgment in areas where current evidence is lacking or insufficient. We think it is important to have evidence-based recommendations to clarify what aspects of practice currently can and cannot be supported by evidence, to encourage use of evidence-based treatments that exist, and to encourage creativity in treatment and research in areas where evidence does not exist. The communities of neurosurgery and neuro-intensive care have been early pioneers and supporters of evidence-based medicine and plan to continue in this endeavor. The complete guideline document, which summarizes and evaluates the literature for each topic, and supplemental appendices (A-I) are available online at https://www.braintrauma.org/coma/guidelines .